IMPACT OF THE DIMENSIONS OF THE QUALITY OF INSTITUTIONS SUCH ON THE FLOW OF FOREIGN DIRECT INVESTMENT TO DEVELOPING ECONOMIES. - Alziyani, Amal Nouri (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
The aim of this study was to examine the effect of the dimensions of the quality of institutions such as: economic quality, political risks, the quality of the financial sector, and the quality of transportation means on the flow of foreign direct investment (FDI) to developing economies. The study was conducted in the most developed 7 economies among the developing countries. In addition, the study also made a comparison between the 7 emerging economies to identify which of them were affected by the established quality determinants for the period from 2002 to 2017. The data were analyzed using the regression model. The results of the study indicate a negative impact of the economic freedom and the quality of the financial sector on the flow of FDI. The study did not indicate the existence of a statistically significant effect to the political risks and the quality of transportation on the flow of FDI.